American Strategy in the War on Terror: An African perspective - Owutu, Innocent Ugochukwu (Advances in Social Sciences Research Journal, 2015)
The terrorist attacks of September 11, 2001, defined the presidency of George W. Bush, who responded by projecting U.S. military power on a global scale. In the months following the attacks, the administration forcefully evicted the Taliban regime and its Al Qaeda sponsors from Afghanistan, while expanding basing rights and military cooperation, for the first time, in Central and South Asia. Indeed, Osama bin Laden is reportedly responsible for a number of these attacks on U.S. government personnel and others during Clinton administration, including the bombings of U.S. embassies in Kenya and Tanzania in 1998 and the attack on the USS Cole in the Yemeni port of Aden in 2000. The study analyzes the various U.S. regimes efforts on the war on terror and its geo- strategic implications especially Africa. In doing this, the study conceptualizes strategy, grand strategy, American national strategy for combating terrorism. It explores the account of the war on terror by U.S. regimes and concludes that Africa’s effort in this regard must remain visible to attract American policy makers